Case report: Birk–Landau–Perez syndrome linked to the SLC30A9 gene—identification of additional cases and expansion of the phenotypic spectrum - Kizhakkedath, Praseetha; AlDhaheri, Watfa; Baydoun, Ibrahim; Tabouni, Mohammed; John, Anne; Almansoori, Taleb M.; Al-Turki, Saeed; Al-Jasmi, Fatma; Alblooshi, Hiba (Frontiers in Genetics, 2023)
Birk–Landau–Perez syndrome (BILAPES) is an autosomal recessive cerebro-renal syndrome associated with genetic defects in the SLC30A9 gene, initially reported in 2017 in six individuals belonging to a large Bedouin kindred. The SLC30A9 gene encodes a putative mitochondrial zinc transporter with ubiquitous expression, the highest found in the brain, kidney, and skeletal muscle. Since the first report, only one additional affected patient has been described, but there were some inconsistencies, such as hearing loss, failure to thrive, and neuroimaging findings between the clinical presentation of the disease in the Bedouin family and the second patient. Here, we present two more patients from a consanguineous Middle Eastern family with features of chronic kidney disease, neurodevelopmental regression, ataxia, hearing loss, and eye abnormalities, which were largely consistent with BILAPES. Whole-exome sequencing detected a homozygous in-frame deletion c.1049_1051delCAG (p.Ala350del) in the SLC30A9 gene, which was the same variant detected in the patients from the primary literature report and the variant segregated with disease in the family. However, in the patients described here, brain MRI showed cerebellar atrophy, which was not a cardinal feature of the syndrome from the primary report. Our findings provide further evidence for SLC30A9-associated BILAPES and contribute to defining the clinical spectrum.